PENGARUH PDB, INFLASI, NILAI TUKAR, HARGA MINYAK DUNIA, HARGA EMAS DUNIA DAN INDEKS NIKKEI 225 TERHADAP INDEKS SEKTOR PERTAMBANGAN PERIODE 2011-2016 - RUSTYANINGSIH, DWI; PURWOHANDOKO (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this research is to analyze the influence of GDP, inflation, exchange rate, world oil price, world goldprice and Nikkei 225 index to mining index period 2011-2016. This type of data is secondary data obtained fromIDX, Indonesian Statistics Center, Bank Indonesia, Investing, London Bullion Market Association (LBMA) andNikkei 225 Official Site. The method of analysis used in this study is multiple linear regression analysis. Partialresearch results show that GDP, inflation, exchange rate and world oil prices do not affect the mining index. GDPis not influential because the increase of GDP does not necessarily increase individual per capita income so it doesnot affect the pattern of investment in the capital market. Inflation did not affect the mining index because inflationoccurring during the study period was still in a mild condition so that the overall price increases were still normal.The exchange rate has no effect as the number of mined exports declines during the study period. World oil pricesdo not affect the index mining because oil is not a commodity that dominates in the mining but coal. While the worldgold price and Nikkei 225 index positively affect the mining index. Then simultaneously all independent variablesaffect the mining index. The magnitude of the effect caused by the world gold price and the Nikkei 225 index is18.5%, while the rest of 81.5% is explained by other variables outside this research. Keywords: LBMA, Nikkei 225 official site